PPO.25 Novel insights from using Stereology based volume estimation of Syncytial nuclear aggregates in Diabetic placenta. (9th June 2014) - Elmoursi, M; Treanor, D; Simpson, NAB
Abstract : Introduction: Placental dysfunction leads to intrauterine compromise and stillbirth. Hypoxia is usually cited as the underlying mechanism in pregnancies complicated by hypertensive disorders, and syncytial deportation (inferred by the presence of syncytial knots) is commonly found on light microscopy. It has been suggested that the same mechanism may underpin intrauterine death in diabetic pregnancy. We set out to test the hypothesis that syncytial knot formation was a more common finding in diabetic pregnancy. Methods: Term placentas were obtained from normal and diabetic pregnant women. Uniform random sampling was undertaken. Blocks were mounted and sections obtained, stained with H&E, then scanned and captured as digitised images. Using customised stereology software eight fields of vision were allocated randomly in every slide and the volumes of the fetal capillaries and of the syncytial knots were estimated. Parametric and non-parametric statistical analysis was used to determine intergroup differences. Results: The volume of the syncytial knots in the placentas of diabetic mothers were significantly reduced compared to normal controls (18.2 vs 39.9 cm 3, P = 0.03, t-test). There was a trend towards an increase in fetal capillary volume in the diabetic group. Conclusions: These results do not support our original hypothesis, in that we found a reduction in syncytial knot volume in diabetics. This suggests that the mechanisms underlying fetal compromise encountered in diabetic pregnancy are unrelated to those governing hypertensive disorders. The study also supports stereology using digital imaging as a useful tool in the quantification of structural placental change.